Evaluating the drought tolerance of five native broadleaf tree species using dendroecological analysis in East Central Europe - Móricz, Norbert; Mészáros, Ilona; Kern, Zoltán; Illés, Gábor Zoltán; Garamszegi, Balázs; Eötvös, Csaba Béla; Berki, Imre; Németh, Tamás Márton (Frontiers in Forests and Global Change, 2025)
Climate change is placing stress on forests, making silvicultural planning more challenging in many temperate regions. Since some major tree species are prone to drought, there is an increasing interest in selecting native broadleaf minor species, which are believed to have greater drought tolerance. Therefore, it is crucial to evaluate the growth performance and vitality of these tree species in the light of the changing climate. Based on tree-ring width data, we analysed the drought response of four minor tree species Acer campestre L., Fraxinus ornus L., Quercus pubescens Willd. and Tilia tomentosa Moench. in relation with a major tree species Quercus cerris L. in different mixed stands along a precipitation gradient in Hungary with the aim to compare the species’ drought tolerance. All the species analysed showed a high drought tolerance, with only minor differences among them. A. campestre, F. ornus and T. tomentosa showed an overall greater climate sensitivity than the oak species, but drought resilience was high in all species. Furthermore, none of the species showed signs of dieback on the study sites with recent climate warming, suggesting that all studied native tree species are also well suited as admixed species in future forest stands.